VALIDATION OF HYBRID LEARNING MODEL DEVELOPMENT USING EMBEDDED SYSTEM - Leni Marlinaa, Nizwardi Jalinusb , Azwar Inrac , Aswandid, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objective of the current research was to measure the validation Hybrid Learning Model development using Embedded System. The research method employed was borg and gall. Model validity test was carried out by experts in learning model, vocational education, media, and linguistics. Research data were collected using a questionnaire. Meanwhile, the data analysis was conducted using model validity test through Akien V test. Based on the results of model validation, it obtained and proved that hybrid learning model using embedded system was valid since it produced valid products in the forms of model books, lecturer manuals, student manuals, application guides, and teaching modules. Keywords: